Institutional Holdings and Payout Policy - GRINSTEIN, YANIV; MICHAELY, RONI (Journal of Finance, 2005)
ABSTRACT We examine the relation between institutional holdings and payout policy in U.S. public firms. We find that payout policy affects institutional holdings. Institutions avoid firms that do not pay dividends. However, among dividend‐paying firms they prefer firms that pay fewer dividends. Our evidence indicates that institutions prefer firms that repurchase shares, and regular repurchasers over nonregular repurchasers. Higher institutional holdings or a concentration of holdings do not cause firms to increase their dividends, their repurchases, or their total payout. Our results do not support models that predict that high dividends attract institutional clientele, or models that predict that institutions cause firms to increase payout.